2014
DOI: 10.1021/ie4032605
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Model of Fractal Aggregate Stability and Restructuring in Shear Flows

Abstract: We combine the analytical theory of nonaffine deformations of noncrystalline solids with numerical Stokesian dynamical simulations to obtain analytical closed-form expressions for the shear modulus of fractal aggregates in shear flows. The proposed framework also provides analytical predictions for the evolution of the fractal dimension d f of the aggregate during the aggregation process. This leads to a lower bound on d f below which aggregates are mechanically unstable (they possess floppy modes) and cannot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 41 publications
(91 reference statements)
1
20
0
Order By: Relevance
“…Notably, the d f values reached in this frame are larger than those observed in stagnant conditions reaching values in the range of 2.4-2.7 [68]. The lower limit of such range, i.e., d f = 2.4, has been recently supported through a mathematical model providing analytical predictions of the aggregate d f during the aggregation process [69].…”
Section: Breakagementioning
confidence: 58%
See 1 more Smart Citation
“…Notably, the d f values reached in this frame are larger than those observed in stagnant conditions reaching values in the range of 2.4-2.7 [68]. The lower limit of such range, i.e., d f = 2.4, has been recently supported through a mathematical model providing analytical predictions of the aggregate d f during the aggregation process [69].…”
Section: Breakagementioning
confidence: 58%
“…Accordingly, the interplay of aggregation and breakage in shear depends strongly on these parameters that clearly affect the resulting cluster d f . An aggregate-stability map, discriminating between clusters restructuring and breakup as a function of the parameters d f , R/a, and _ γ (fractal dimension, cluster size over primary particle radius and shear rate), has been recently presented [69]. Further efforts in this direction, e.g., focusing on an experimental validation of these results would be of great value.…”
Section: Shear Rate Primary Particle Sizementioning
confidence: 99%
“…With the simulation approach used for these calculations, this value has been set by the limiting of the cluster structure, which is somehow elusive and usually semi-empirical 45 . Such simulations would also be extremely time-consuming.…”
Section: Comparison With Experimental Data 1 Viscosity and Cluster Rmentioning
confidence: 99%
“…They found that in shear flow, the aggregates tended to have high fractal dimension by means of experiment [1], numerical simulation [6] and analytical model [7]. Further studies showed that the breakup behavior of the high fractal dimension aggregate was significantly diverse [4,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies showed that the breakup behavior of the high fractal dimension aggregate was significantly diverse [4,[7][8][9]. One of the reason is that the aggregate with high space-filling properties may have the connectivity of the particle vary, leading to different ways in force distribution and propagation.…”
Section: Introductionmentioning
confidence: 99%